Experimental Study of Operating Indicators of a Thermalactic Covering Panel - Dikarev, K.B.; Kuzmenko, O.M.; Petrenko, V.O.; Sankov, P.M.; Kyslytsia, L.V.; Ibadov, N. (Science and Innovation, 2024)
Introduction. The use of solar energy in construction is widespread due to a rapid growth in energy tariffs. Problem Statement. The share of building roof in the heat consumption during a heating season accounts for 10-25%. In summertime, intensive heating of a large roof area leads to a high room temperature and, therefore, active use of air conditioning systems. Purpose. The purpose is to develop an experimental sample of thermosetting roof panel containing a material with phase transformation and to study the operational parameters of the sample in summertime. Further, the roof panel is planned to be used as additional source of heating or air conditioning to improve the temperature balance of microclimate inside the building. Materials and Methods. The field study was conducted in July 2018 on a pilot sample of thermosetting roof panel containing a material with phase transformation in a metal casing protected by a copper roofing sheet and an effective heater. Results. When performing experimental study of the thermosetting roof panel, a temperature difference (between the inlet and the outlet) that varies from 1.2 to 4 °C for 10 h 45 min has been observed. The presence of material with phase transformation can reduce the roof sheet temperature about two times: the M01 detector has recorded a maximum temperature of 87.8°C, in the case of material with phase transformation, and 43.7°C, in the case without the use of the mentioned material. Conclusions. The experiment has shown that in summertime the use of the material with phase transformation reduces twice the temperature of the copper sheet of the roof panel inner surface. The use of such technology is advisable to reduce the cost of energy for air conditioning indoor, enables construction of energy-saving environment friendly residential and industrial buildings.